2009
DOI: 10.1016/j.jep.2009.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Antiinflammatory and antinociceptive activities of Blechnum occidentale L. extract

Abstract: The results described here are the first report of pharmacological studies of Blechnum occidentale L. and indicate that this plant has antinociceptive and antiinflammatory activities which support its folk medicine use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…58,97 Other ferns, including Equisetum arvense, Cyathea phalerata, and Blechnum occidentale, have also been shown to display anti-inflammatory and antioxidant activity due to the presence of secondary metabolites like phenolic compounds. 98,99 Over the duration of this study, no deaths occurred in any of the experimental groups. Moreover, the extracts did not induce morphological variations or any toxic signs in the animal subjects.…”
mentioning
confidence: 91%
“…58,97 Other ferns, including Equisetum arvense, Cyathea phalerata, and Blechnum occidentale, have also been shown to display anti-inflammatory and antioxidant activity due to the presence of secondary metabolites like phenolic compounds. 98,99 Over the duration of this study, no deaths occurred in any of the experimental groups. Moreover, the extracts did not induce morphological variations or any toxic signs in the animal subjects.…”
mentioning
confidence: 91%
“…Pain induced by formalin test represents two distinct phase, early phase of formalin test represents centrally mediated pain, while the late phase pain indicates pain mediated by a peripheral effect via release of transmitters such as histamine, serotonin, prostaglandins, kinins, etc. (Nonato et al, 2009). Results indicated that the extract produced better activity in second phase, therefore analgesic effects of the extract might be mediated through a peripheral mechanism rather than a central mechanism.…”
Section: Discussionmentioning
confidence: 89%
“…(Otsuka et al, 1972), Cheilanthes farinosa (Yonathan et al, 2006), Cyathea gigantea (Fig. 3c) (Benjamin and Manickam, 2007;Madhukiran and Ganga Rao, 2011), Blechnum occidentale (Nonato et al, 2009), D. mariesii (Chang et al, 2007b), Microsorum scolopendria (Bloomfield, 2002), Phyllitis scolopendrium (Bonet and Valles, 2007), and P. leucotomos (Lucca, 1992). In addition, wound healing activity has been reported for many species of ferns such as D. solida (Whistler, 1992), Polystichum pungens (Grierson and Afolayan, 1999), A. evecta (Cambie and Ash, 1994), Nephrolepis cordifolia (Fig.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%